Study on Aerodynamic Characteristics of Flapping Wings Motion Mode. (February 2019) - Wang, Cui; Wang, Hongde; Sun, Jiangbo; Liu, Qiang
Abstract: Flapping Wing Micro Aerial Vehicle (FWMAV) is a new type of M AV simulating the flight of insects or birds. FWMAV can generate lift and thrust simultaneously to achieve the function of lifting, forward flying or hovering by only flapping wings. It also can change flight mode flexibility by adjusting flapping parameters, which makes it have nice maneuverability and high flight efficiency and more suitable for military mission. So it has great development and research value. In this paper, insect is selected as biomimetic research object, using the computational fluid dynamics method to make a numerical study on aerodynamic characteristics of flapping wings motion mode.